Rhythmic E-box binding by CLK-CYC controls daily cycles in per and tim transcription and chromatin modifications. - Taylor, P.; Hardin, P.E. (Molecular and Cellular Biology, 2008)
The Drosophila melanogaster circadian oscillator comprises interlocked per/tim and Clk transcriptional feedback loops. In the per/tim loop, CLK-CYC-dependent transcriptional activation is rhythmically repressed by PER or PER-TIM to control circadian gene expression that peaks around dusk. Here we show that rhythmic transcription of per and tim involves time-of-day-specific binding of CLK-CYC and associated cycles in chromatin modifications. Activation of per and tim transcription occurs in concert with CLK-CYC binding to upstream and/or intronic E-boxes, acetylation of histone H3-K9, and trimethylation of histone H3-K4. These events are associated with RNA polymerase II (Pol II) binding to the tim promoter and transcriptional elongation by Pol II that is constitutively bound to the per promoter. Repression of per and tim transcription is associated with PER-dependent reversal of these events. Rhythms in H3-K9 acetylation and H3-K4 trimethylation are also associated with CLOCK-BMAL1-dependent transcription in mammals, indicating that the mechanism that controls rhythmic transcription is a conserved feature of the circadian clock even though feedback repression is mediated by different proteins.